Implementation Policy of ITF (Inflation Targeting Framework) Bank Indonesia on Inflation Rate In Indonesia - Sukardi, Agung Slamet (MALIA: Journal of Islamic Banking and Finance, 2023)
Inflation is the effect of a long economic crisis that hit a country. Inflation is a condition in which prices continue to rise. The purpose of this study was to determine the effect of the money supply, interest rates, and exchange rates on inflation in the period 2000-2018. The type of data in the discussion of quantitative data and sourced from secondary data 2000-2018. Data analysis used multiple linear regression and data collection techniques with samples that were in accordance with the purpose of the assessment and adapted to the characteristics of the study. The results of the F test show that there is a significant effect of the ITF policy using the money supply, exchange rate and interest rates on inflation suppression. The t test results show that the interest rate variable has an effect on inflation. In other words, the interest rate variable partially has a positive effect on inflation. For the government to be more careful and pay attention to the monetary policies taken in relation to the money supply, exchange rates and interest rates in influencing inflation.